Retaining volunteers in African communities with specific reference to the Cancer Association of South Africa - Lombard, A; Modise, VM (Social Work/Maatskaplike Werk, 2002)
This article reports on a study on the retention of volunteers for CANSA in African communities. Whilst social workers had no problem recruiting volunteers for CANSA to assist in service rendering, it was difficult to retain them. From the research findings, as well as an in-depth literature study, it was concluded that in order to retain volunteers, there are specific processes and factors that need to be taken into account before and after volunteers are recruited.